2010
DOI: 10.1097/mcc.0b013e32833cb874
|View full text |Cite
|
Sign up to set email alerts
|

Admission and discharge of critically ill patients

Abstract: The decisions to admit and discharge patients depend on patient, structure and physician-related variables. Early ICU admission of the critically ill patient is beneficial. Future analysis should also investigate economic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 36 publications
0
32
0
1
Order By: Relevance
“…This process of recognition has much value; however, without a specific plan for the prevention of clinical worsening of vulnerable patients, it may constitute an insufficient strategy to improve relevant patient outcomes. Moreover, the risk of ICU readmission for patients discharged from ICU is heterogeneous (2,4). The specific risk factors require specific prevention strategies, such as early removal of invasive devices to prevent nosocomial infections in patients who needed invasive monitoring or treatment (23); early pulmonary rehabilitation to avoid respiratory failure in patients with chronic respiratory diseases (24) and implementation of specific rehabilitation programs focused on recovery of functional abilities for patients with ICU-acquired muscular weakness with the aim of avoiding clinical worsening related to poor functional status (25).…”
Section: Editorialmentioning
confidence: 99%
“…This process of recognition has much value; however, without a specific plan for the prevention of clinical worsening of vulnerable patients, it may constitute an insufficient strategy to improve relevant patient outcomes. Moreover, the risk of ICU readmission for patients discharged from ICU is heterogeneous (2,4). The specific risk factors require specific prevention strategies, such as early removal of invasive devices to prevent nosocomial infections in patients who needed invasive monitoring or treatment (23); early pulmonary rehabilitation to avoid respiratory failure in patients with chronic respiratory diseases (24) and implementation of specific rehabilitation programs focused on recovery of functional abilities for patients with ICU-acquired muscular weakness with the aim of avoiding clinical worsening related to poor functional status (25).…”
Section: Editorialmentioning
confidence: 99%
“…Besides the severity of illness score, there is also an association between nursing workload and post-ICU mortality [65,66] . The Therapeutic Intervention Scoring System (TISS) has been widely applied to assess workload and resource allocation in intensive care, measuring treatment intensity [67][68][69] . Consequently, attempts have been made to use TISS scores to categorize the level of care that patients require and even to evaluate the care required after ICU discharge [1,68] .…”
Section: Readmission?mentioning
confidence: 99%
“…Consequently, attempts have been made to use TISS scores to categorize the level of care that patients require and even to evaluate the care required after ICU discharge [1,68] . Several authors have shown an association of the TISS value of the last ICU day with post-ICU mortality [65,66,69,70] and therefore indirectly the association with ICU readmission. Smith et al [66] concluded in their research that the mean TISS scores in patients readmitted to the ICU were significantly higher than in patients who did not require readmission [65,66] .…”
Section: Readmission?mentioning
confidence: 99%
“…Desafortunadamente, en la literatura anglosajona existen muy pocos estudios que definan el alta de esta manera, sino que la incluyen en la acepción más amplia de alta que se efectúa en horario no laboral (after-hours), programada o no 16 , con lo que las comparaciones presentan limitaciones. Un aspecto clave a nuestro juicio en el estudio de este tema es el establecimiento de definiciones y criterios precisos para el tipo de alta, pues más que si está o no programada o el momento en que se produce, debiéramos poder distinguir entre precoz y tardía en función de lo apropiado de esta 17 .…”
Section: 008unclassified